Four patients with Sillence type I osteogenesis imperfecta and mild bone fragility, complicated by left ventricular cardiac valvular disease and cardiac tissue fragility caused by type I collagen mutations. Issue 2 (5th December 2013) - Vandersteen, Anthony M.; Lund, Allan M.; Ferguson, David J.P.; Sawle, Philip; Pollitt, Rebecca C.; Holder, Susan E.; Wakeling, Emma; Moat, Neil; Pope, F. Michael
Abstract Osteogenesis imperfecta (OI) type I is a hereditary disorder of connective tissue (HDCT) characterized by blue or gray sclerae, variable short stature, dentinogenesis imperfecta, hearing loss, and recurrent fractures from infancy. We present four examples of OI type I complicated by valvular heart disease and associated with tissue fragility. The diagnosis of a type I collagen disorder was confirmed by abnormal COL1A1 or COL1A2 gene sequencing. One patient was investigated with electrophoresis of collagens from cultured skin fibroblasts, showing structurally abnormal collagen type I, skin biopsy showed unusual histology and abnormal collagen fibril ultra‐structure at electron microscopy. The combined clinical, surgical, histological, ultra‐structural, and molecular genetic data suggest the type I collagen defect as contributory to cardiac valvular disease. The degree of tissue fragility experienced at cardiac surgery in these individuals, also reported in a small number of similar case reports, suggests that patients with OI type I need careful pre‐operative assessment and consideration of the risks and benefits of cardiac surgery. © 2013 Wiley Periodicals, Inc.